The Effectiveness of Contextual-Approach Science E-Module Integrated with Local Wisdom on Pressure Topic to Improve Critical Thinking Skills - Hidayat, Edy; Marwoto, Putut; Widiyatmoko, Arif (Universitas Negeri Semarang, 2024)
Integrating local wisdom into science materials is a crucial effort to create contextual learning and instill noble values and a sense of cultural appreciation. Each region requires education tailored to its unique characteristics for effective educational development, necessitating a contextual approach. Incorporating local wisdom values is an essential step in this process. This study aims to develop a contextual science e-module that integrates local wisdom to enhance students' critical thinking skills. The research employed a Research and Development (R&D) approach, specifically using the Sugiyono model. The results indicated that the e-module received a validation score of 97% from material experts, categorized as very valid, and 96% from media experts, also categorized as very valid. The practicality test assessment yielded a value of 98% and was rated as very practical, and student feedback resulted in a score of 98%, which was deemed very good. Additionally, the effectiveness of the e-module was evaluated through the N-Gain score for critical thinking skills, which averaged 0.83, placing it in the high category. The N-Gain value for students' critical thinking skills was 89.95%, classified as effective. Based on the validation, readability, practicality, and effectiveness assessments, the contextual-approach science e-module integrated with local wisdom is deemed feasible as a learning resource.